Association of lncRNA-p53 regulatory network (lincRNA-p21, lincRNA-ROR and MALAT1) and p53 with the clinicopathological features of colorectal primary lesions and tumors - Chaleshi, Vahid (Oncol Lett, 2020)
Colorectal cancer (CRC) is a common intestinal cancer with a high mortality rate. Early detection of this type of cancer is fundamental to the prevention of the disease, which results in improved survival rates. In the human colon tissue, transition from normal epithelium to adenoma is considered to be caused by unknown molecular incidents occurring over 5–10 years. The detection of CRC has proved problematic when in the early stages of disease. In addition, identifying suitable biomarkers for the detection of CRC progress in patients remains one of the most significant challenges. Long non-coding RNAs have been demonstrated to contribute to the promotion of CRC. The aim of the present study was to investigate the clinical and biological significance of long intergenic non-coding (linc)RNA-p21, lincRNA-regulator of reprogramming (ROR) and metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in the colon tumor and polyp tissue, and the association that these have with the expression of p53 at the mRNA level. Neoplastic and paired adjacent normal tissue samples were obtained from 72 patients (46 polyps and 26 tumors). Reverse transcription-quantitative PCR was performed to determine the relative fold changes in the expression of lincRNA-p21, lincRNA-RoR, MALAT1 and p53 in the samples. A significant association was observed between the levels of MALAT1 and p53 in neoplasm tissues (R=0.073; P<0.05). The relative expression of the MALAT1 gene revealed a statistically significant difference between the different polyp types and number of polyps (P=0.0028 and 0.022, respectively). Adjuvant therapy in patients with tumors revealed an association between the levels of lincRNA-ROR and lincRNA-p21 expression (P=0.015 and 0.038, respectively). MALAT1 may be selected as an early detection biomarker for CRC. Furthermore, lincRNA-ROR and lincRNA-p21 may serve as prognostic and therapeutic biomarkers in patients with CRC.